2022
DOI: 10.32604/iasc.2022.019892
|View full text |Cite
|
Sign up to set email alerts
|

Fusion-Based Supply Chain Collaboration Using Machine Learning Techniques

Abstract: Supply Chain Collaboration is the network of various entities that work cohesively to make up the entire process. The supply chain organizations' success is dependent on integration, teamwork, and the communication of information. Every day, supply chain and business players work in a dynamic setting. They must balance competing goals such as process robustness, risk reduction, vulnerability reduction, real financial risks, and resilience against just-in-time and cost-efficiency. Decision-making based on share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(35 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Both the skills are inclusive of home control skill, accounting and finance skill, communal skills, security and fitness, and sporting skill, among others [28] and [29]. Initial reports show that SPA will acquire the user's choices, records, and facts, for instance, etymology, conduct, behavior, words, and searches using search engine optimization and machine learning techniques to make them more proficient and shrewder with time [30]. Succinctly, the choices and information, among others, are the ones that are vulnerable to attacks from enemies [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both the skills are inclusive of home control skill, accounting and finance skill, communal skills, security and fitness, and sporting skill, among others [28] and [29]. Initial reports show that SPA will acquire the user's choices, records, and facts, for instance, etymology, conduct, behavior, words, and searches using search engine optimization and machine learning techniques to make them more proficient and shrewder with time [30]. Succinctly, the choices and information, among others, are the ones that are vulnerable to attacks from enemies [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proper management of sustainable supply chain operations plays an undeniable role in environmental sustainability and positively impacts societies (Manavalan and Jayakrishna 2019 ). They were adequately designing and managing the sustainable flow of products and services from raw material to finished goods is considered significant in the circular economy (Waqas et al 2021 ; Khan et al 2020 ; Ali et al 2022 ). In recent years, literature review confirmed that plenty of research articles had been published by researchers on SSCM corresponding to the green technological innovations (Wangsa et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…in which different market actors work jointly to execute supply chain operations, is of particular importance for e-commerce, where most organizations prefer to cooperate with reliable and sustainable companies. Ali et al presented a fusion-based SCC solution [ 56 ], which utilized Support Vector Machine (SVM) and kNN algorithms. The authors also conceptualized a framework for effectively tackling disruption risks.…”
Section: Resultsmentioning
confidence: 99%